2021
DOI: 10.3389/fneur.2021.654143
|View full text |Cite
|
Sign up to set email alerts
|

SENSE-Cog Asia: A Feasibility Study of a Hearing Intervention to Improve Outcomes in People With Dementia

Abstract: Background: There are few evidence-based non-pharmacological interventions adapted for people with dementia (PwD) in lower- and middle-income countries (LMIC). Thus, there is value in culturally adapting existing interventions from other settings. One such intervention for PwD involves hearing rehabilitation, which may improve dementia-related outcomes.Objective: To culturally adapt and evaluate the feasibility and acceptability of a multi-faceted hearing support intervention to enhance quality of life in PwD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, study recruitment, timely hearing aid delivery, procedures for arranging home visits, and communication between referring clinicians and the study team were identified as areas in need of improvement. 70 …”
Section: Modifiable Risk Factors For Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, study recruitment, timely hearing aid delivery, procedures for arranging home visits, and communication between referring clinicians and the study team were identified as areas in need of improvement. 70 …”
Section: Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…Preliminary findings from Pakistan demonstrated positive feasibility, acceptability, and tolerability of the intervention by study participants. However, study recruitment, timely hearing aid delivery, procedures for arranging home visits, and communication between referring clinicians and the study team were identified as areas in need of improvement 70 …”
Section: Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…The 'Balanced Partnership for Dementia Research Checklist' (Table 3), when applied to two ongoing dementia studies with LMIC-HIC collaborations 35,36 revealed scores of 18 out of a total score of 27 (66% of the total score) and 16 out of a total score of 22 (5 'not applicable' items, thus the total score was lower; 72% of the total score), respectively, where a higher score is better. The higher percentage score attained by the Brazil-France study reflects a greater maturity of the collaboration achieved over time and greater awareness of the recommendations outlined in our Charter of Conduct.…”
Section: Checklist For Researchersmentioning
confidence: 99%
“…To test the utility of the checklist, we applied it to two existing LMIC‐HIC dementia research collaborations, the SENSE‐Cog Asia project, 35 which is adapting a sensory support intervention for people with dementia in three South Asian countries (Bangladesh, India and Pakistan) in collaboration with UK investigators, and a data‐mining collaborative study on Theory of Mind in Alzheimer disease, conducted between colleagues in Brazil and France 36 …”
Section: Approach To Developing a Charter Of Conductmentioning
confidence: 99%